Effect of Virus Antibody on Infection of Mouse Brain by Mount Elgon Bat Virus - Patel, J. R. (Journal of Medical Microbiology, 1982)
SUMMARY Intranasal inoculation of mice aged 1-6 days with Mount Elgon bat virus produced an acute brain infection and death of all the mice at 5-7 days after inoculation. Virus multiplied in the olfactory bulbs and spread to the midbrain and then hindbrain, reaching titres of 109-1010 plaque forming units/g of wet tissue. Fatal disease was prevented by administration of virus antibody after infection, which was then restricted to the olfactory bulbs. Antibody was ineffective when infection was established in the midbrain; it reduced infectivity by about 99% in olfactory bulbs but by only a small fraction in midbrain and hindbrain. The findings may reflect differences in virus maturation and spread, and the accessibility of virus antibody to the olfactory bulbs, midbrain and hindbrain.